Teaching styles and achievement: student and teacher perspectives - Hidalgo Cabrillana, Ana (My University, 2017)
We analyze the relationship of the teaching style with student achievement. As a novelty, we explore whether the e˙ect of the teaching style di˙ers when class work is reported by teachers or students. We find that who reports the practices matters. Teamwork and student discussions -modern practices- are strongly related to better achievement, and individual work and rote learning -traditional practices- are detri-mental. But these e˙ects are significant only using students’ reports. Heterogeneous e˙ects of teaching practices arise by subject or gender, but mostly using students’ reports, suggesting di˙erences in the perception of teaching styles. Only results by socioeconomic status are robust to who reports practices: students from low socioe-conomic background lose from traditional teaching and gain from modern teaching.
Keywords: Estudio y enseñanza; Teaching Styles; Student Achievement